Preventing Disease
XXX, 478 p.
Keywords: Preventing Disease, the offspring of an extraordinary collaboration between the U.S. and Canadian Preventive Services Task Forces, presents a meticulous and objective review of the published evidence on preventive measures. Examining such diverse and relevant topics as screening for endometrial cancer, exercise counselling for healthy adults, and the evidence for a causal relation between dietary lipids and coronary heart disease, this volume reflects the editors' shared conviction that recommendations for preventive action should rarely exceed what is well justified by the evidence. In the current period, characterized as the Second Public Health Revolution, the authors' hard-nosed approach leads them to ask the tough questions. Are preventive measures cost-saving? Does preventive screening actually lead to treatment in clinical practice? Does the treatment do more good than harm? To what extent does our desire to eliminate causes of serious disability, ill health and premature death cloud our objectivity? All concerned about preventive medicine, community health, and primary care will find valuable stimulation for thought and action in this book: the contributions have gone beyond the rhetoric.